Efectos adversos de consecuencia fatal por tratamiento con fármacos antituberculosos. - RODRIGUEZ HURTADO, Diana Carmela; RAMIREZ CUENTAS, John Helmut; PACHECO SALAS, Victor Hugo; SALAZAR SALAS, Lucía Esther; CASALINO CARPIO, Ernesto; LIZARZABURU LIZARZABURU, Luis; KEMPER VASQUEZ, Roberto (Revista Médica Herediana, 2013)
We report the case of a patient with several adverse effects, of fatal consequence, associated with drugs used in the treatment for Tuberculosis. Patient was hospitalized at the Hospital Nacional Arzobispo Loayza of Lima, Peru, since May until July 2001. We identified the presence of several adverse effects associated with antituberculosis drugs (dermatitis, nausea, vomit, interstitial nephritis, hepatitis for drug and thrombocytopenia, associated with Intracraneal hemorrhage, of fatal consequence). This study reports a case very infrequent in the world (including Peru), in relation with the presence of several adverse effects of antituberculosis drugs, in the same patient, who died because of these effects. We want to inform the potential risks associated with antituberculosis drugs (of great use in Peru for the high prevalence of Tuberculosis), that must have a regimen and adequate control to avoid severe consequences. ( Rev Med Hered 2002; 13: 148-152 ).